Elaboration of reference material for cadmium and arsenic in hydrobiological products, for the purpose of being used in a laboratory intercomparation program - Sandoval, Soraya; González, Karina; Muñoz, Luis Humberto (Revista do Instituto Adolfo Lutz, 2021)
Reference materials (RM) are tools used in the comparability and traceability of measurements. They are widely used by laboratories for method validation and quality control of assay. Chile must evaluate the performance of laboratories that analyzing metals in fishery products, despite RM have high prices and are scarce. For that reason, a RM in a hydrobiological product was developed. Reference values for arsenic and cadmium elements for a fishmeal were assigned. The measurement methods for characterization of the material were Inductively Coupled Plasma Mass Spectrometry, Atomic Absorption Spectrometry and Neutron Activation Analysis. Reference values with their expanded uncertainty (U) were established for arsenic 2.64 ± 0.42 mg/kg (U; k = 2) and for cadmium 0.86 ± 0.16 mg/kg (U; k = 2). Homogeneity and stability of the RM allowed its use in a proficiency test for eleven food control laboratories. Results for median were 2.114 mg/kg for arsenic, and 0.863 mg/kg for cadmium. The performance values of the participants were evaluated with a z score obtaining 60% satisfaction for arsenic and 73% for cadmium. The material demonstrated to be suitable for use in interlaboratory proficiency assay.